Significance of the Activities of Choshu-men towards the Realization of the Meiji Restoration (Part 1: Outline) - Dr. Ikumatsu Fujimoto (Significance of the Activities of Choshu-men towards the Realization of the Meiji Restoration (Part 1: Outline), 2021)
The main purpose of this book is to clarify the significance of the actions of Choshu-men (people whose hometowns are in the present Yamaguchi prefecture) from the perspective that human history is God’s providence to save humanity. The book proceeds as follows. we first summarize the many Choshu-men’s activities before and after the Meiji Restoration (i.e., the change from the Tokugawa Shogunate system, a feudal society with four social positions — soldiers (samurai), farmers, artisans, and merchants — controlled by the samurai, to the constitutional monarchy and parliamentary system led by the Meiji emperor, which, in principle, envisioned equality for all people). It will focus particularly on Shoin Yoshida and Shinsaku Takasugi, who established the foundation to fundamentally contribute to the realization of the Meiji Restoration at the risk of losing their own lives. It is indispensable to investigate how the tradition of giving one’s life for the nation at a time of national crisis was formulated and inherited by the later generations of Choshu-men. Therefore, we also briefly reference the remarkable actions of three Choshu prime ministers after World War II who inherited this spirit. Next, we give a general overview of the reality of the modern world from the perspective that the true nature of today’s global situation comes from the strong confrontation of the forces of good and evil, centered on globalism. Following that, we interpret the modern world briefly based on the historical viewpoint that the history of humankind is God’s providence of salvation, which is clearly shown in the Exposition of the Divine Principle written by Rev. Sun Myung Moon. Finally, we try to clarify the modern-day significance of the actions of Choshu-men from the perspective that human history is God’s providence to save humanity. As an appendix, we briefly give a general view of the Mori clan and the Choshu Domain that drew out the activities of the Choshu-men during the Meiji Restoration.